ACE and ACTN3 Gene Polymorphisms and Genetic Traits of Rowing Athletes in the Northern Han Chinese Population - Wei, Qi (Frontiers in Genetics, 2021)
This investigation aimed to explore the effects of ACE I/D and ACTN3 R577X gene polymorphisms on specific quantitative variables, including height, weight, arm span, biacromial breadth, forced vital capacity (FVC), FVC/weight, maximal oxygen uptake (VO2max), prone bench pull (PBP), loaded barbell squat (LBS) and 3000-meter run, in 243 Chinese rowing athletes. The ACE and ACTN3 genotypes were obtained for each athlete via polymerase chain reaction (PCR) on saliva samples, and the genotype frequency was analyzed. The ACE genotype frequency of rowing athletes were 45.8% II, 42.2% ID and 12% DD for males and 33.6% II, 48% ID, 18.4% DD for females. There were significant differences in weight in male athletes, PBP in female athletes, and ACE genotypes. A linear regression analysis using PBP and LBS as different dependent variables and ACE genotypes as independent variables based on the ACE I allele additive genetic effect showed statistical significance in female athletes (p<0.05). There was a significant difference in the distribution of the three genotype among male athletes (36.7% XX, 38.5% RX and 24.8% RR, χ2=5.191, df=2, p=0.022<0.05). There were no significant differences in the distribution of the three genotypes among female athletes (23.8% XX, 47.8% RX, 28.4% RR, χ2=0.24, df=2, p=0.619>0.05). The ACTN3 gene polymorphism of male rowing athletes was dominated by the ACTN3 577X allele. There were significant differences in the χ2 test between groups of male athletes. The ACTN3 R577 allele was dominant in female athletes. There were significant differences between PBP and FVC/body weight and ACTN3 genotypes in male athletes by ANOVA, respectively (p<0.05). A linear regression analysis using FVC and FVC/body weight as dependent variables and ACTN3 genotypes as independent variables based on the ACTN3 577X allele recessive genetic effect showed statistical significance in male athletes (p<0.05). These results suggested that ACE and ACTN3 gene polymorphisms may be used as biomarkers of genetic traits in Chinese rowing athletes.